Modelagem de fluxo para quebra de barragem via método das características e dinâmica de fluidos computacional - Bueno Neto, Urias de Moura (2021)
As the literature shows, the frequency of accidents involving the breaking of dams is becoming increasingly higher. In the last decade, Brazil was marked by the tragedy of Mariana and Brumadinho, which generated great environmental and socioeconomic impacts, with the main loss of human lives being lost. Due to the complexity and severity of a possible catastrophe involving dams, modeling for the failure of a hypothetical dam was performed, comparing an approach already widely used for 1-D and 2-D flows, where the Saint-Venant Equations were solved, also known as shallow water equations, using the method of characteristics, through a code elaborated in the MATLAB ® software, the results were compared with the data obtained from computational fluid dynamics, using the ANSYS ® software that solves the Reynolds-Averaged Navier-Stokes equations by the finite volume method, to verify if a less robust approach like the one produced in MATLAB, has advantages over a more robust approach like the one in ANSYS. In general, good depth results were obtained when comparing both methods with the highest error in the order of 24%, highlighting the agility and low computational cost of the method of characteristics in obtaining them, about speeds, the desired result was not obtained due to the high order of errors, however, the wave propagation speed was identical in both approaches when evaluating the generated wave profile. The aim of reducing errors related to speeds in sections may be the objective of future research.